Competency Development of Science and Technology Human Resources at the National Research and Innovation Agency (BRIN): Analysis of International Scientific Publication Collaboration - Meiningsih, Siti (Universitas Syiah Kuala, 2023)
The National Research and Innovation Agency (BRIN) was formed based on Presidential Regulation no. 78 of 2021, to improve the quality of research results in the country. It is hoped that this agency will be able to boost the wheels of research in Indonesia through the integration of research, development, study, application, as well as invention and innovation activities so as to accelerate the mastery of science and technology for the sake of the nation's progress. Using descriptive qualitative methods, this research aims to analyze: (1) the development of science and technology human resource competencies through international scientific publications at BRIN and, (2) collaboration of research organizations in producing international scientific publications. The research results show that there is a correlation between the increase in the number of international scientific publications and the development of science and technology human resource competencies. In producing international scientific publications, collaboration is formed between various research organizations and non-research organizations at home and abroad. For research organizations, this collaboration also has an impact on obtaining external funding from within and outside the country.